Effect of hazelnut oil on hematological parameters and liver histopathological changes induced by naproxen in local male mice - Mohammed Abed Mahmood (Kufa Journal for Veterinary Medical Sciences)
This study designed to identify the outcome use of naproxen on hematological parameters and liver histopathological changes and the effect of hazelnut oil on these parameters in local male mice. Eighteen mice were divided equally into three groups: and each group involved of 6 mice. The first group is control group which received distal normal saline while the second group was treated with naproxen at 20 mg/kg of mice body weight. The third was group treated with hazelnut oil 3g/kg of mice body weight, after two hours followed by naproxen 20 mg/kg of mice body weight. The experimental study continues for 21 days. The hematological results exhibited a significant decrease in WBC, RBC, hemoglobin and hematocrit at P <0.05 in the second group treated with naproxen compared to the control group. The third group treated with hazelnut oil followed by naproxen showed a significant increase in hemoglobin and hematocrits at P <0.05 compared to the second group but the hematological values in the third group did not show a significant difference compared to the control group. The histopathological results showed normal liver histology in first group the end of the experimental study. The second group which was received the naproxen showed congestion of blood vessels, hemorrhage inflammatory cells infiltration, necrosis and the presence of Kupffer cells. The third group showed a histological appearance of the liver relatively similar to the control group. The hazelnut oil improved the hematological parameters in this study and preserved the histological structures of the liver from being affected by naproxen.